If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x-x=53
We move all terms to the left:
15x-x-(53)=0
We add all the numbers together, and all the variables
14x-53=0
We move all terms containing x to the left, all other terms to the right
14x=53
x=53/14
x=3+11/14
| 8x12=8x(+) | | 6/7w=20/4/7 | | /5(x-2)=1/10(x+6) | | 2y+1=y+49 | | 4.3x-1.5=24.3 | | w+5.31=9.26 | | 6/7w=204/7 | | 3x+11=3x | | 25+x=15x-3 | | -13x-14=66 | | 17m-15=6m-10+11m | | 1.9x=7.6 | | -17c+8=-16-19c | | 2x+12=10x-18 | | 12-w=-16+6w | | 12−w=–16+6w | | 6m=3/8 | | 7x+5x-16=180 | | .17x+3.2=5.75 | | 9.2-4w=-2(3w+5 | | -7+(1+8d)=26 | | 45=12u-7u | | 1/2x+2+x+1/2x+2+x=40 | | .71x=180 | | 2x-7=13x+18 | | -2(3-j)=7+3j | | 4x+.16=3.32 | | 4-8=9a+7 | | 5/7x=180 | | 2(x–1)–4=2(x+1)–3 | | 4/3=m+4/1 | | 62=11x-26 |